Multimodal literacies : An introduction - Albers, Peggy; Sanders, Jennifer (Literacies, the arts, & multimodality, 2010)
This article introduces K-college educators to current research and instructional practices for including a wider range of experiences that help teachers explore how a curriculum rich in these experiences can benefit students personally and academically. Editors Peggy Albers and Jennifer Sanders argue that we all learn best when engaged in complex, socially constructed, and personally relevant creative composition and interpretation of texts.
Keywords: enseignement; multimodalité